The Paradox of Welfare in Tourism Villages: A Sociological Analysis of Child Labor in Kuta Mandalika - Bagus Kagum Pardyansa; Lalu Muhammad Nafi' Rabbani; Rara Intana Putri; Jepri Utomo; Mila Noviana (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2026)
The rapid growth of tourism not only has a positive impact on the community’s economic growth but also gives rise to social issues, such as an increase in the number of underage children working as street vendors and accessory sellers in tourist areas. This study aims to analyze the impact of tourism on underage child labor and to identify the factors that cause children to become involved in such economic activities. This study employs a qualitative approach using the case study method. Data collection techniques involved direct observation and in-depth interviews with child workers, parents, and the local community in the Kuta Mandalika tourist area. The results indicate that family economic factors are the primary cause of children working in the tourist area. Work activities take place after school until the afternoon, thereby reducing children’s time for studying and playing.